Bahasa Indonesia: Bahasa Indonesia - Akhmad Rofii Damyati; Ridwan, Ridwan (STAI Al-Mujtama Pamekasan, 2024)
This article examines the development of the negative framing of Islam as an intolerant religion within contemporary discourse, particularly in Western media. Through a historical and analytical approach, this study reveals that accusations of intolerance towards Islam often overlook the rich intellectual history of Islam, characterized by a diversity of thought and openness to knowledge from other civilizations. Since the classical era, Muslim scholars such as Al-Khwarizmi and Ibn Sina have demonstrated intellectual tolerance by adapting and integrating foreign knowledge through the process of